Enhancing the Compressive Strength Property of Gypsum used in Walls Plastering by Adding Lime (Journal of University of Babylon for Engineering Sciences, 2018)
This study aims to improve the compressive strength and the adhesive for the Iraqi gypsum by using the lime as a local material to improve the properties of the Iraqi gypsum in binding and plastering works. The lime was used to replace 10%, 20%, and 30% of the total gypsum quantity to study the development of the paste material and its effect on the compressive strength, its structure and the water quantity. The initial and final setting time was conducted with the compressive strength test. The results showed a full improvement in the compressive strength for the cubes at the age of 7 days comparing to the gypsum paste. There was a change in the setting time with the replacement of gypsum with lime in addition to the increase in the density of the final product. The results showed the possibility of developing the Iraqi product and the recommendation to use in a wide range in the finishing works which can be more economic in the work.